If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(y + 6) = 6 + 8y Reorder the terms: 9(6 + y) = 6 + 8y (6 * 9 + y * 9) = 6 + 8y (54 + 9y) = 6 + 8y Solving 54 + 9y = 6 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 54 + 9y + -8y = 6 + 8y + -8y Combine like terms: 9y + -8y = 1y 54 + 1y = 6 + 8y + -8y Combine like terms: 8y + -8y = 0 54 + 1y = 6 + 0 54 + 1y = 6 Add '-54' to each side of the equation. 54 + -54 + 1y = 6 + -54 Combine like terms: 54 + -54 = 0 0 + 1y = 6 + -54 1y = 6 + -54 Combine like terms: 6 + -54 = -48 1y = -48 Divide each side by '1'. y = -48 Simplifying y = -48
| 7+4(5x-6)=5-3(2x+1) | | -10x+15=6x+3 | | 3(x+2)=1 | | (4v-7)(1-v)=0 | | 6q-1=-p+20 | | 5x+3x+4=-12 | | 7(z+4)=6z | | 12(x-3)=-6-6 | | 3x/5+7/2=x/10 | | 5y-9=6y-1 | | T/10=3/35 | | A=Ao/2n | | 3/4=w/18 | | 3(2x-5y)-2(x-3y)= | | 2(3+x)=19 | | -9(y-1)=-8y-6 | | 3/4=w/35 | | -7(-2y+4)-y=4(y-3)-1 | | y=0.95x+6 | | 22-13x=-8-2x-18x | | sen(x)+2cos(x)=1 | | 6x-8=5x+90 | | 3x-40=x-18 | | 5p-3p-30=-18 | | 4x+4=31-5x | | 8x-9+x=180 | | 2x-5+x=2 | | 3x+4=84-5x | | 3x+84=10x+14 | | 2x+17=45-2x | | =5.6e | | 6mn(m+1)= |